Ceramic-based nanocomposites: A perspective from carbonaceous nanofillers. (June 2022) - Sharma, Nidhi; Saxena, Tuhina; Alam, Syed Nasimul; Ray, Bankim Chandra; Biswas, Krishanu; Jha, Shikhar Krishn
Abstract: To overcome the inherent brittle nature of ceramics and to optimize their favorable properties, new design philosophies and novel concepts for manufacturing are needed. Owing to their distinguished mechanical attributes such as strength and stiffness, developing ceramic matrix composites (CMCs) has become the latest penchant for researchers. CMCs are traditionally fibers dispersed in a ceramic matrix (oxide or non-oxide). With the advent of nanoparticles, the probing interests in the field of CMCs are now transforming from traditional reinforcement media (microscale fillers) into new possibilities at the nanoscale. This has brought a new generation of CMCs at nanometric level, commonly known as ceramic matrix nanocomposites (CMNCs). Introduction of nanomaterials like graphene and carbon nanotubes (CNTs) as nano-reinforcements has modified the ceramic-structures at the nanometric level for advanced applications in fields such as automotive, industrial, and aerospace engineering. Lately, a variety of new strategies such as tuning in the presence of dopants, opting pristine dispersion routes and usage of modified sintering techniques have enhanced the distinctive features of the CMNCs. This work summarizes the ongoing advances, recent research, key challenges in the implementation of carbonaceous CMNCs reinforced with graphene and CNTs along with their applications and future prospects. A detailed discussion on the sintering techniques, tribological behavior, strengthening and toughening mechanisms of carbonaceous CMNCs is presented. Various advantages of CMNCs reinforced with graphene and CNTs along with a few drawbacks like the cost and process-limitations have been elaborated. Graphical Abstract: Ceramic-Based Nanocomposites Reinforced by Carbonaceous Nanofillers. ga1 Highlights: A comprehensive and critical review on effect of carbonaceous nanofillers on ceramic matrix nanocomposites (CMNCs). A review of the sintering processes and strengthening mechanisms of CMNCs reinforced by carbonaceous nanofillers. A summary of the advances and key challenges in the implementation of CMNCs reinforced with carbonaceous nanofillers.